Culture Bites: A reality of food truck in Klang Valley Malaysia - Abdullah, Norhidayah; Ishak, Noriza; Saad, Mazni; Abukhalifeh, Alaa Nimer; Bujang, Aisah (e-International Publishing House, Ltd., UK., 2022)
Cleanliness is an important element towards customer’s satisfaction. This study aims to investigate the relationship between cleanliness attributes (product quality, food premise & food handlers' cleanliness) towards customers hygiene satisfaction. An online survey being conducted among 116 customers in Klang Valley. The data were analysed using SPSS Software version 26. Food premise, food handlers' cleanliness and product quality associated to customers’ hygiene satisfaction. Of all, food product quality was the most significant predictor. The results obtained may contribute to the cleanliness practices among food truck food handlers and as a basis for cleanliness practice for Malaysia Food Truck Association.